The Process of Critical Thinking in Teaching Foreign Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article deals with the process of critical thinking in teaching foreign language. Critical thinking is associated with quality thinking and, if sufficiently developed, provides learners with a more skillful way of communicating with other people, acquiring new knowledge, and dealing with ideas, beliefs, and attitudes. In all these areas language plays a crucial role.